2001
DOI: 10.1097/00000539-200102000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring End-Tidal Carbon Dioxide During Weaning from Cardiopulmonary Bypass in Patients Without Significant Lung Disease

Abstract: End-tidal carbon dioxide tension (PETCO(2)) changes with fluctuations in cardiac output (CO). We compared PETCO(2) to pulmonary artery blood flow (PAQt) during weaning from cardiopulmonary bypass (CPB) in normothermic patients without significant pulmonary disease. Fifteen consecutive adult cardiac surgical patients were prospectively studied during and shortly after weaning from CPB. Before separation from CPB, PETCO(2) and PAQt were measured, the latter by transesophageal Doppler echocardiography. At the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
9
0
3
Order By: Relevance
“…Capnography may be a guide to optimize therapy during cardiopulmonary resuscitation 12,13 and to evaluate the quality of cardiac massage 13 or of post-resuscitation prognosis 14,15 . A previous study has shown direct correlation between end tidal CO 2 (P ET CO 2 ) changes and cardiac output measured by thermodilution 16 . This study has observed direct correlation between P ET CO 2 and cardiac output at CPB weaning.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Capnography may be a guide to optimize therapy during cardiopulmonary resuscitation 12,13 and to evaluate the quality of cardiac massage 13 or of post-resuscitation prognosis 14,15 . A previous study has shown direct correlation between end tidal CO 2 (P ET CO 2 ) changes and cardiac output measured by thermodilution 16 . This study has observed direct correlation between P ET CO 2 and cardiac output at CPB weaning.…”
Section: Discussionmentioning
confidence: 95%
“…A capnografia pode ser um guia para otimizar a terapêutica durante a reanimação cardiorrespiratória 12,13 e como um avaliador de qualidade da massagem cardíaca 13 ou do prognóstico pós-reanimação 14,15 . Em estudo anterior foi demonstrada uma correlação direta entre as alterações da fração expirada de dióxido de carbono (P ET CO 2 ) e o débito cardíaco medido por termodiluição 16 . Nesse estudo foi observada uma correlação direta entre a P ET CO 2 e o débito cardíaco no período de saída de circulação extracorpórea.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…2,3 Also, in our study, cardiac output and ETCO 2 measurements were performed simultaneously. Fluid responders had a significant change in their cardiac output and ETCO 2 following the PLR maneuver, which is a well-recognized method to assess fluid responsiveness.…”
Section: To the Editormentioning
confidence: 99%